ANALYSIS OF SATU DATA INDONESIA POLICY IMPLEMENTATION: THE ROLE OF BPS-STATISTICS INDONESIA AS A STATISTICAL DATA COACH - Resti Amelia; Amy Sri Yayuk Rahayu (JURNAL DARMA AGUNG, 2023)
Satu Data is a program idea from the Government of Indonesia to improve data management so that it can support targeted policy making. To achieve this, open, accurate, and interoperable government data is needed. One of the data covered by the One Data Indonesia policy is statistical data, where the data supervisor is the Central Statistics Agency (BPS). BPS as a statistical data development agency must guide other agencies so that the implementation of statistical activities can run well. The purpose of this study is to determine the implementation of Indonesia's One Data policy so far, especially in terms of the role of the Central Statistics Agency as a statistical data coach in supporting the one data policy. The research method used is descriptive-qualitative. Data collection techniques are carried out by collecting data secondarily and primarily. Meanwhile, the data analysis technique of this study uses Edward III's theory where there are four variables in analyzing the implementation of Indonesia's One Data policy. The results of the study based on four variables in Edward III's theory, namely communication, resources, disposition, and bureaucratic structure, show that the implementation of One Data Indonesia has not gone well. Likewise, the role of BPS is still not optimal in fostering agencies and local governments to manage statistical data.